(untitled) - The Chronic Poverty Research Centre (CPRC) (United Kingdom, 2008)
Through our research we identify five main traps that underpin chronic poverty – insecurity, limited citizenship, spatial disadvantage, social discrimination and poor work opportunities – and outline key policy responses to these. It is our hope that this report will inspire deeper reflection on how to tackle chronic poverty effectively and – most of all – will stimulate action to make it happen.
Keywords: Food shortage,Thiếu lương thực,Poverty alleviation,Development research,Giảm nghèo,Nghiên cứu phát triển